2020
DOI: 10.21608/javs.2020.85584
|View full text |Cite
|
Sign up to set email alerts
|

Impact Of Continuous Treatment With Propylthiouracil On Renal And Hepatic Functions In Rabbits

Abstract: This study was designed to investigate the effect of continuous treatment with the anti-thyroid drug, propylthiouracil (PTU), on renal and hepatic functions in rabbits as an experimental animal model. Animals were randomly divided into four different isolated groups (n = 10); Group I received normal saline. Group II, III, and IV were daily administrated with PTU in oral dosing of 50, 75, and 150 mg/kg, BWT, respectively, for three successive weeks. Serum T 3 and T 4 levels were measured in all groups. Increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…In addition, the current study's histopathological examination revealed several abnormalities in the liver tissue of GII animals. These results are in agreement with [23,27]. The PTU is commonly used to induce hypothyroidism experimentally [28].…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the current study's histopathological examination revealed several abnormalities in the liver tissue of GII animals. These results are in agreement with [23,27]. The PTU is commonly used to induce hypothyroidism experimentally [28].…”
Section: Discussionsupporting
confidence: 89%
“…While Farrag et al . [ 33 ] explained that the drug caused the changes should be listed among “drugs-induced liver injury”. The latter type of drugs defined as “drug-induced critical alterations of hepatocytes that trigger the immune systems of susceptible hosts to infiltrate their livers and assault/damage hepatocytes, which leads to liver injury”.…”
Section: Discussionmentioning
confidence: 99%